Mechanical performance of a hybrid zirconia developed through hydrothermal treatment and Room-Temperature Atomic Layer Deposition (RT-ALD) - Bastos-Bitencourt, Natália Almeida; Soares Bombonatti, Juliana Fraga; Bitencourt, Sandro Basso [UNESP]; Hatton, Benjamin D.; De Souza, Grace Mendonca (Elsevier, 2021)
Objective: A silica-based nanofilm has been successfully deposited via Room-Temperature Atomic Layer Deposition (RT-ALD) on the surface of a glass. The purpose of this study was to evaluate the mechanical performance of a hybrid interface created between yttria-stabilized zirconia (Y-PSZ) transformed layer and silica-based nanofilm via RT-ALD. Material and methods: Fully-sintered Y-PSZ (14 × 4.0 × 1.5 mm) specimens in different translucencies (MO, MT, LT; IPS e.max Zircad, Ivoclar Vivadent) were distributed in 5 groups: control (C - no treatment); hydrothermal treatment (HT- 15h, 134°C, 2 bar); alumina blasting (B - 50 μm Al2O3); RT-ALD silica deposition (S); HT followed by silica deposition (HTS). RT-ALD cycles consisted of the sequential exposure of specimens to tetramethoxysilane orthosilicate (TMOS - 60s) and ammonium hydroxide (NH4OH - 10 min) vapors in 40 cycles. Mechanical performance was analyzed by flexural strength (FS) (n = 10) and fatigue failure load (staircase method; n = 20) tests. Surface hardness (H) and Young's modulus (YM) were analyzed by nanoindentation. For surface chemical and topographical characterization, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) were performed. Data from surface H, YM, FS, and fatigue limit (FL) were analyzed by two-way analysis of variance (ANOVA). Results: The interaction between material and treatment had a significant effect on FS (p < 0.001). The FS values ranged from 436.23 MPa to 856.65 MPa. HT resulted in the highest FS (856.65 MPa) for LT and the lowest FS (436.23 MPa) for MO zirconia. For all materials, S and B treatments resulted in similar FS values (p > 0.410). S did not affect FL when compared to the C group (p > 0.277) for any material investigated. HTS resulted in higher FL than S for LT and MO materials (p < 0.001). Surface hardness and modulus were similar between control and S-treated specimens for all materials analyzed. XPS analysis showed homogeneous silica content after 20 and 40 RT-ALD cycles, and SEM did not show significant changes in surface morphology between C and S-treated specimens. Conclusion: RT-ALD resulted in effective silica deposition without any deleterious effect on zirconia-based materials mechanical properties. Alumina blasting promoted higher alteration on surface topography. HT prior to S resulted in superior FL (for MO and MT) and flexural strength (MO) for some of the materials investigated.
Keywords: Dental ceramics; Flexural strength; Hybrid layer; Nanoindentation; Phase transformation